Addressing fault tolerance in 4-PAM signaling by using block codes for on/off-chip communication - Forooshani, Arash Abtahi; Rokhani, Fakhrul Zaman (IEEE, 2011)
The AWGN channel is characterized and verified for 4-PAM signaling. Based on that, three fault tolerant on/off-chip communication architectures using block codes alongside 4-PAM modulation have been evaluated. The results display decent improvement in BER performance while keeping complexity as low as possible.